A fluorinated indole‐based MDM2 antagonist selectively inhibits the growth of p53wt osteosarcoma cells. (16th February 2019) - Skalniak, Lukasz; Twarda‐Clapa, Aleksandra; Neochoritis, Constantinos G.; Surmiak, Ewa; Machula, Monika; Wisniewska, Aneta; Labuzek, Beata; Ali, Ameena M.; Krzanik, Sylwia; Dubin, Grzegorz; Groves, Matthew; Dömling, Alexander; et al.
Abstract : The p53 protein is engaged in the repair of DNA mutations and elimination of heavily damaged cells, providing anticancer protection. Dysregulation of p53 activity is a crucial step in carcinogenesis. This dysregulation is often caused by the overexpression of negative regulators of p53, among which MDM2 is the most prominent one. Antagonizing MDM2 with small molecules restores the activity of p53 in p53 wild‐type (p53 wt ) cells and thus provides positive outcomes in the treatment of p53 wt cancers. Previously, we have reported the discovery of a panel of fluoro‐substituted indole‐based antagonists of MDM2. Here, we demonstrate the biological activity and stereoselectivity of the most active compound from this series. Both enantiomers of the esterified form of the compound, as well as its corresponding carboxylic acids, were found active in fluorescence polarization (FP) assay, nuclear magnetic resonance (NMR) and microscale thermophoresis (MST) assay, with K i and K D values around 1 μm . From these four compounds, the esterified enantiomer ( R )‐5a was active in cells, which was evidenced by the increase of p53 levels, the induced expression of p53‐target genes ( CDKN1A and MDM2 ), the selective induction of cell cycle arrest, and selective growth inhibition of p53 wt U‐2 OS and SJSA‐1 compared to p53 del SAOS‐2 cells. The analysis of the crystal structure of human MDM2 in complex with the compound ( R )‐6a (carboxylic acid of the active ( R )‐5a compound) revealed the classical three‐finger binding mode. Altogether, our data demonstrate the activity of the compound and provide the structural basis for further structure optimization. Abstract : MDM2 antagonists restore the activity of p53 in p53 wild‐type (wt) cancer cells. Here we demonstrate the biological activity and stereoselectivity of trifluoro‐substituted indole‐based MDM2 antagonist synthesized by multicomponent Ugi reaction. The compound activates p53, induces cell cycle arrest, and selectively inhibits the growth of p53(wt) U‐2 OS and SJSA‐1 cells compared to p53(del) SAOS‐2 cells.